Optimization of Ibuprofen Nanosponges Herbal Gel for Anti-Inflammatory Action - Dr. D. Prasanthi (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The main purpose of the research was to formulate Ibuprofen nanosponges herbal gel to reduce the inflammation in rheumatoid arthritis patients. Materials and Methods: The emulsion solvent diffusion method was used to formulate ibuprofen nanosponges using a 3-factor, 3-level Box-Behnken design. A Box-Behnken design was selected with X1, X2, and X3 (quantity of ethyl cellulose, quantity of PVA, and speed, respectively) as factors and (ex vivo drug release, entrapment efficiency, and production yield) as responses which resulted in 15 runs. After running with 15 formulations, they were optimized according to physico-chemical characterization. Further, it was prepared and evaluated. Results: After evaluation, the following results were obtained: percent production yield (82.9 ± 0.43%), entrapment efficiency (88.1 ± 0.46%), permeation studies (43.2 ± 0.28% in 6 h), and flux (1.63 ± 0.3 μg/cm2/h). SEM studies showed the spherical shape with nano-sized pores, particle size (214.3 nm diameter), zeta potential (−37.8 mV), and PDI (0.341). PNS was formulated into gel with 5% tea tree oil and was evaluated. The optimized gel formulation (G3) showed a viscosity of 4.1487 × 105cps and ex vivo release of 24.64 ± 47.72% after 6 h, follows 1st order kinetics and anomalous release mechanism. The optimized gel formulation and marketed diclofenac sodium gel were studied for anti-inflammatory studies for 4 h. By measuring the paw edema in a rat animal model, edema reduction in 4 h shows 0.2 ± 0.1 cm which is equal to control. Conclusion: It was found that ibuprofen nanosponges herbal gel reduces the inflammation in rheumatoid arthritis.